2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7592162
|View full text |Cite
|
Sign up to set email alerts
|

Classification of squat quality with inertial measurement units in the single leg squat mobility test

Abstract: Many assessment and diagnosis protocols in rehabilitation, orthopedic surgery and sports medicine rely on mobility tests like the Single Leg Squat (SLS). In this study, a set of three Inertial Measurement Units (IMUs) were used to estimate the joint pose during SLS and to classify the SLS as poor, moderate or good. An Extended Kalman Filter pose estimation method was used to estimate kinematic joint variables, and time domain features were generated based on these variables. The most important features were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Eleven studies investigated the utilisation of wearable IMU systems for quantifying exercise technique [3,19,23,64,[69][70][71][72][73][74][75]. Table 10 summarises the sensing set-ups, movement measure which was classified, methodology and performance metrics for each system identified in this area.…”
Section: Movement Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies investigated the utilisation of wearable IMU systems for quantifying exercise technique [3,19,23,64,[69][70][71][72][73][74][75]. Table 10 summarises the sensing set-ups, movement measure which was classified, methodology and performance metrics for each system identified in this area.…”
Section: Movement Classificationmentioning
confidence: 99%
“…STROBE = STrengthening the Reporting of OBservational studies in Epidemiology. [69], [60] Single sensor units (n=19) [14], [52], [58], [24], [53], [7] [67], [70], [71], [72], [73], [74] Charlton et al…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…In the pilot data analysis [14] , we found the ankle IR features to be the best predictors of the DKV, which led us to suggest that it is possible to use only one sensor on the tibia (saving time and simplifying the test protocol) and still have good classification accuracy. To confirm this hypothesis with the larger datasets, we used feature selection on only ankle extracted features (90 out of 210 features) and found that ankle IR velocity, angle and acceleration, as well as ankle Add velocity features are the best predictors in the absence of hip or knee information.…”
Section: Resultsmentioning
confidence: 89%
“…In our pilot study [14] , we classified SLS performance as “poor,” “moderate” or “good” based on clinically understandable features. In the study, 3 IMUs were attached to the shank, thigh and low back of 7 healthy volunteers who performed 5 consecutive repetitions of SLS.…”
Section: Related Workmentioning
confidence: 99%
“…Research in this field has shown the ability of multiple body-worn IMUs to evaluate exercise quality for a variety of exercises [ 11 - 14 ]. These range from early-stage rehabilitation exercises such as heel slides and straight leg raises [ 15 ] to more complex late-stage rehabilitation exercises or S&C exercises such as bodyweight squats [ 16 ], lunges [ 17 ], and single-leg squats [ 18 - 20 ]. More cost-effective and practical systems using a single body-worn IMU have also been shown to be effective in the analysis of exercise technique [ 17 , 18 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%